The perfect fit diet : how to lose weight, keep it off, and still eat the foods you love - Sanders, Lisa (New York, 2006)
In what O magazine voted the best program in its diets roundup, Sanders presents a science-based, customized weight-loss plan that works for life. The key is a questionnaire that covers everything from medical histories to which foods just taste good and satisfy hunger
Keywords: Food preferences; Reducing diets